PENGARUH GOOD GOVERNANCE DAN PENGENDALIAN INTERN TERHADAP KINERJA PEMERINTAH KABUPATEN PELALAWAN - Nur Azlina; Ira Amelia (Universitas Jember, 2014)
This purpose of this research is to examine the effect Good Governance and Internal Control on Goverment Performance at Pelalalawan Regency. The population in this study is middle and bottom managers at SETDA Pelalawan Regency. Data that is used in this research is primary data, that was collected by survey techniques by distributing questionnaires. Linear regression analysis was used as the method of analysis. The results of this research showed all variables are valid, reliable and fullfil clasic asumption. The result of hypotheses analysis show that Good Governance and Internal Control have positive and significance effect on on government performance at Pelalawan Regency Keywords: good governance, internal control, local government performance.